Effect of an Ethanolic Fruit Extract of Xylopia Aethiopica and its Major Alkaloid, Xylopic Acid, on Learning and Memory: A Pre-Clinical Evaluation from a Neuropharmacological Perspective - Koomson, A.E. (University of Ghana, 2018)
Background: Cognitive dysfunction, presenting as learning and memory impairment, is a common manifestation in many chronic diseases, including depression, epilepsy and Alzheimer’s disease. It could also be present without any known underlying medical condition. Till date, no drug has shown convincing efficacy in improving learning and memory deficits in these conditions although some medicinal plants are demonstrating promising effects. The aim of the study was to investigate the effect of fruit extract of Xylopia aethiopica and its kaurene derivative, xylopic acid, on learning and memory using animal models. Materials and Methods: Xylopia aethiopica fruits were collected, dried and extracted using 70% v/v ethanol. Xylopic acid was isolated and purified from the fruits. ICR mice (20-25 g) were grouped, after which they received oral doses of fruit extract of Xylopia aethiopica (30-300 mg/kg), xylopic acid (30-300 mg/kg), standard nootropics [citicoline (30, 100, 300 mg/kg) or piracetam (30, 100, 300 mg/kg)], ketamine (30 mg/kg) or saline as vehicle. The animals were then taken through Morris water maze test which measured hippocampally-dependent spatial learning and memory, spontaneous alternation Y-maze test that measured spatial working memory and spatial recognition memory and novelty object recognition test which measured exploratory learning and recognition memory. Contributions of GABAergic and cholinergic neurotransmission in the mechanism(s) of action of the extract and xylopic acid were also investigated. Results: The fruit extract of X. aethiopica (XAE) and xylopic acid (XA) enhanced learning and memory by increasing the percentage exploration with the novel object in the novelty object recognition test, percentage alternation in the spontaneous alternation Y-maze test. In contrast, both did not increase the change in escape latency of the Morris water maze test but increased the percentage frequency in the probe trial. Pre-treatment with scopolamine hydrobromide (1 mg/kg, i.p) did not reverse the learning and memory enhancing ability of XAE and XA. Pre-treatment with diazepam (1 mg/kg) reversed the learning and memory enhancing ability of XAE and XA, suggesting involvement of GABAergic pathway. Conclusion: The fruit extract of Xylopia aethiopica and xylopic acid are potential candidates for improving exploratory learning and recognition memory, spatial working memory, spatial recognition memory and reference memory. The fruit of Xylopia aethiopica and xylopic acid acts through the GABAergic pathway.
MPhil.
Keywords: Ethanolic Fruit; Xylopia Aethiopica; Acid; Neuropharmacological